2013
DOI: 10.5430/ijfr.v4n4p140
|View full text |Cite
|
Sign up to set email alerts
|

Does Working Capital Management Matter in Dividend Policy Decision? Empirical Evidence from Nigeria

Abstract: This study examines the relationship between dividend payout ratio and working capital management and the effect of firm's working capital management practice on its dividend payout ratio. The working capital management is measured by the net trade cycle, current ratio and debt ratio. The data used in this study were obtained from twelve manufacturing companies quoted on the Nigeria Stock Exchange between 2002 and 2006. The data wer analysed using the Pearson product moment correlation technique and ordinary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…As previous noted, a number of past studies have examined the effect of firm-level characteristics, such as size, cash flow, leverage and profitability on dividend policy (Valipour, Rostami & Salehi 2009;Okpara 2010;Hunjra 2011;Jagannathan & Marakani, 2011;Oladipupo & Ibadin 2013;Mirbagherijam 2014). By contrast, studies examining the extent to which corporate governance mechanisms affect dividend policy are generally scarce, but particularly acute in the case of SMEs (Thanatawee, 2012;Abor & Fiador, 2013;Arshad et al, 2013;Ghasemi et al 2013;Iqbal 2013;Mansourinia et al 2013).…”
Section: Empirical Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As previous noted, a number of past studies have examined the effect of firm-level characteristics, such as size, cash flow, leverage and profitability on dividend policy (Valipour, Rostami & Salehi 2009;Okpara 2010;Hunjra 2011;Jagannathan & Marakani, 2011;Oladipupo & Ibadin 2013;Mirbagherijam 2014). By contrast, studies examining the extent to which corporate governance mechanisms affect dividend policy are generally scarce, but particularly acute in the case of SMEs (Thanatawee, 2012;Abor & Fiador, 2013;Arshad et al, 2013;Ghasemi et al 2013;Iqbal 2013;Mansourinia et al 2013).…”
Section: Empirical Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The high yielded dividend policy aims to satisfy the investor, bringing the conflicts to a minimum level while easing the management's responsibility of maintaining high liquidity of cash flow. Having sacrificed for lacking the operational funding, the management has the confidence to obtain low capital cost (Oladipupo & Ibadin, 2013). Because of the negative consequences on the working capital, this policy can be used to estimate the market price in future periods (Zuo, 2015), where future market value is a new indicator of predicting the expected return in the future.…”
Section: The Relationship Between Dividend Policy and Future Market Valuementioning
confidence: 99%
“…However, profitability and collateral could not explain dividend payments. Oladipupo and Ibadin (2013) in establishing the relationship between working capital management and dividend policy in Nigeria employed listed manufacturing companies with data covering 2002-2006. Using the ordinary least squares, the findings revealed that profitability and working capital management (in terms of net trade cycle) have a positive insignificant relationship with dividend policy while earnings and firm growth related negatively and insignificantly with dividend policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study follows the model used by Oladipupo and Ibadin (2013) and Yakubu (2016) with some modifications based on the selected variables. This is specified as follows:…”
Section: Model Specification and Data Analysismentioning
confidence: 99%